ANALISIS PENGEMBANGAN SMART VILLAGE DI DESA TEGAL HARUM KECAMATAN DENPASAR BARAT KOTA DENPASAR - Putri, Ni Putu Dinda Kalpika (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2025)
This research explores how the smart village concept is developed and implemented in Denpasar City, focusing on Tegal Harum Village located in West Denpasar District. The study is grounded in the growing emphasis on digitalizing village governance in Bali as part of regional development strategies adapting to technological transformation and the post-toursim era. A descriptive qualitative approach was employed, with data collected through observation, in depth interviews, and documentation. Nine informants were selected through purposive sampling, consisting of representatives from the Denpasar City Development Planning Agency (Bappeda), the Community and Village Empowerment Office (DMPD), the West Denpasar Sub-district Office, and local government officials and residents of Tegal Harum Village. The findings indicate that the village government has implemented various digital innovations, including public service applications, data-based administrative systems, and digital media promotion of local potential. These initiatives have improved service efficiency and governance transparency, earning recognition at city and national levels. However, community participation remains limited due to habitual patterns, cultural challenges, and digital literacy challenges. The study concludes that the success of smart village initiatives depends not only on technological and policy readiness but also in the social, cultural and adaptive capacities of local communities in navigating digital transformation. Keywords: Community Participation; Rural Digitalization; Smart Village